1998
DOI: 10.1002/(sici)1096-9861(19980511)394:3<271::aid-cne1>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Birth and fate of proliferative cells in the inner nuclear layer of the mature fish retina

Abstract: In teleost fish, unlike other vertebrates, the retina continues to grow throughout the animal's life both by stretching of the mature tissue and by the addition of new cells. Following larval development, new retinal cell birth is known to occur in a rim at the periphery of the mature retina and in the outer nuclear layer (ONL). We have now found that cell birth and proliferation also occurs in the inner nuclear layer (INL) of the mature fish retina. In rainbow trout (Onchoryncus mykiss), proliferative cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 0 publications
4
60
1
Order By: Relevance
“…In this study, [ 3 H]thymidine labeling revealed elongated, mitotically active clusters of cells that appeared to migrate along the processes of Müller glia from the ONL to the INL. More recent experiments have confirmed the existence of this neurogenic cell population in teleost retinas of rainbow trout (Julian et al, 1998), goldfish (Otteson et al, 2001), and zebrafish (Stenkamp, 2004). The proliferative cells in the INL divide slowly, and so had not been consistently seen following intraocular injection of BrdU.…”
Section: B the Rod Photoreceptor Lineagementioning
confidence: 83%
See 1 more Smart Citation
“…In this study, [ 3 H]thymidine labeling revealed elongated, mitotically active clusters of cells that appeared to migrate along the processes of Müller glia from the ONL to the INL. More recent experiments have confirmed the existence of this neurogenic cell population in teleost retinas of rainbow trout (Julian et al, 1998), goldfish (Otteson et al, 2001), and zebrafish (Stenkamp, 2004). The proliferative cells in the INL divide slowly, and so had not been consistently seen following intraocular injection of BrdU.…”
Section: B the Rod Photoreceptor Lineagementioning
confidence: 83%
“…The second cell type also found in the INL has a spindle-shaped fusiform nucleus and migrates toward the ONL along Müller glia processes. The two types of proliferative inner nuclear cells have been referred to as PINCs (Julian et al, 1998). The third cell type of the rod lineage is the rod precursor, which is located in the ONL and has an ovoid nucleus.…”
Section: B the Rod Photoreceptor Lineagementioning
confidence: 99%
“…4C). Note that the number of PCNA ϩ cells in the WT retinas varies between the 2 mutant lines and across experiments; this variability in the absolute rate of cell proliferation in teleost fish retinas is typical (32) and likely ref lects environmental modulation of endogenous growth rates. Taken together, these data suggest that nbl blocks cone photoreceptor regeneration at an earlier step compared with ncp and are consistent with the differential time course of hspd1 and mps1 expression during retinal regeneration.…”
Section: Hspd1 and Mps1 Are Required For Zebrafish Cone Photoreceptormentioning
confidence: 99%
“…The teleost retina exhibits persistent neurogenesis throughout its life from two distinct cellular sources (Johns, 1977;Otteson and Hitchcock, 2003). Stem cells scattered throughout the inner nuclear layer (INL) produce the rod precursor cells found in the outer nuclear layer (ONL), which are restricted to only differentiate into rods during persistent neurogenesis (Johns, 1982;Julian et al, 1998;Otteson et al, 2001). A stem cell population located at the circumferential marginal zone (CMZ) produces all of the remaining cell types (Johns and Easter, 1977;Johns, 1982).…”
Section: Introductionmentioning
confidence: 99%